MIF, a controversial cytokine: a review of structural features, challenges, and opportunities for drug development. (1st December 2016) - Bloom, Joshua; Sun, Shan; Al-Abed, Yousef
ABSTRACT: Introduction: Macrophage migration inhibitory factor (MIF) has emerged as a promising drug target in diseases including sepsis, rheumatoid arthritis, and cancer. MIF has multiple properties that favor development of specific, targeted therapies: it is expressed broadly among human cells, has noted roles in diverse inflammatory and oncological processes, and has intrinsic enzymatic activity amenable to high-throughput screening. Despite these advantages, anti-MIF therapy remains well behind other cytokine-targeted therapeutics, with no small molecules in the pipeline for clinical development and anti-MIF antibodies only recently beginning clinical trials. Areas covered: In this review we summarize current literature regarding MIF structure and function–including challenges and controversies that have arisen in studies of anti-MIF therapeutics–and propose a strategy for development of clinically relevant anti-MIF drugs. Expert opinion: We believe that the field of anti-MIF therapeutics would benefit from capitalizing on the protein's multiple assets while acknowledging their flaws. The tautomerase enzymatic site of MIF may not be active biologically, but can nonetheless offer a high-throughput method to highlight molecules of interest that can affect its other, frequently intertwined bioactivities. Future work should also focus on developing more robust assays for MIF bioactivity that can be used for second-pass screening and specificity studies.